Avaliação de um sistema de neuro-órtese sEMG-FES: um estudo de caso em pacientes neurológicos - González Méndez, María Verónica (2024)
Injuries and neurological conditions correspond globally to the leading cause of disability, thus impacting the independence and autonomy of affected individuals to carry out their daily living activities. Many of the tasks present in daily living activities involve the use of the upper limbs; thus, compromising the function of this limb is a significant factor impacting quality of life. Recovery of hand-arm function may involve conventional therapies and assistive technologies. However, the application of these technologies in the literature presents a much greater focus on specific populations such as Stroke and Spinal Cord Injury (SCI) and in a particular stage of the injury (acute and subacute ). Thus, a scarcity of studies has been generated addressing the applicability of these technologies in populations with chronic injuries and other types of neurological conditions. Given this, in this study, a sEMG-FES interface of the neuro-orthesis type was applied, not wearable in individuals with chronic neurological injuries. The present study is cross-sectional and uncontrolled, with a convenience sample whose participants were recruited through the Pequeno Cotolengo Health Complex. A total of 10 meetings were held, two days of evaluation (pre and post-intervention), and eight interventions. The interventions consisted of the application of electrical stimulation triggered by sEMG when performing a functional movement. The sEMG data were collected in the triceps brachii and extensor carpi radialis muscles both on the evaluation days and before and after each intervention. Three volunteers were recruited, and they completed all interventions. In addition, video recordings were made before and after each intervention of each participant. The sEMG signals were filtered using the Empirical Mode Decomposition method, and time and frequency domain characteristics were evaluated. Video analysis was performed using Kinovea software to verify the minimum and maximum elbow and wrist extension angles for each intervention. The application of sEMG-FES neuro-orthesis had effects not only on the stimulated muscles (extensor carpi radialis) but also on the triceps brachii. These effects were also visualized in the video analysis with the angles of the elbow and wrist joints when compared between the pre and post-moments of each intervention. In this way, there was an effect mainly associated with the resistance to fatigue of the muscles involved in the reaching movement on the applicability of the neuro-orthesis in individuals with chronic neurological sequelae with impairment of the upper limbs.